IONIC LIQUID-POLYMERIZED POLYBENZIMIDAZOLE MEMBRANES FOR ALKALINE FUEL CELL APPLICATIONS - Chairuna, Annisa
Recently, the development of anion exchange membranes (AEM) for alkaline fuel cell applications has been made to overcome issues related to the use of liquid KOH as the electrolyte. Early AEM studies have been focused on the ammonium quaternized polymers prepared through chloromethylation of the commercial available polymer. However, low ionic conductivity, thermal and chemical stability of the membrane are still obstacles that need to be improved. Another major issue is related to the preparation of this anion exchange membrane. Indeed, the use of toxic and expensive compounds in the preparation method is also an important problem that has to be overcome to pave the way of AEM commercialization for alkaline fuel cell applications. In this work, a novel anion exchange membrane, namely [2-(Methacryloyloxy) ethyl tri methyl ammonium]-polymerized PBI membrane (abbreviated as MTAC-polymerized PBI membrane), has been prepared for uses as anion exchange membrane in alkaline fuel cell applications. A new synthetic approach in the preparation method has been carried out with the use of non-toxic and inexpensive compounds. Attempts also have been made to develop the feasibility of the method and the characteristic properties of the membrane. A pristine porous PBI membrane was used as the membrane support, while quaternary ammonium-based ionic liquid (MTAC) was employed as the charge carrier. The pores of pristine PBI membrane were filled with MTAC followed by graft polymerization of MTAC onto PBI backbone. The viability of the method was confirmed and optimized. The chemical structure and the characteristic properties of the membrane were also studied. It is found that the hydroxide ionic conductivity of the membrane reached 10.58•10-3 S•cm-1 at room temperature. The membrane exhibited an exceptional tolerance in hydroxide solution with the concentration below than 6 M. The membrane showed good thermal stability at temperature below than 2300C. The single cell performance test has been evaluated. However, no relevant polarization curve was obtained and some hypotheses have been enounced. In the future, some optimization, characterization, and modification of the method have to be done to improve the membrane performance for uses as AEMs in AFC applications.